SITCARE: AN IOT-BASED SITTING BEHAVIOR MONITORING SYSTEM USING SENSOR FUSION - Kevin Sutanto; Putri Caezylia Rundupadang; Louie Jason Liman; Jeremiah Jacob Hartadhi; Yohanes Panca Sihite (Universitas Lampung, 2026)
Prolonged sitting and poor sitting posture have become significant occupational health concerns among office workers, contributing to musculoskeletal disorders, fatigue, and reduced work productivity. This study proposes SITCARE, an Internet of Things (IoT) based office sitting behavior monitoring system that integrates an FSR402 pressure sensor, an MPU6050 gyroscope, and an HC-SR04 ultrasonic sensor using a sensor fusion approach. The proposed system continuously monitors sitting duration, chair inclination, and seat height, while transmitting real time sensor data to a Firebase Realtime Database for web-based visualization. In addition, an automated Telegram chatbot provides reminders to encourage regular breaks and adequate hydration. The developed system was evaluated through sensor validation, communication performance testing, system functionality assessment, and user acceptance evaluation. Experimental results demonstrated reliable sensor operation, stable cloud communication with an average round trip latency of 220 ± 50 ms and zero packet loss, as well as successful real time dashboard visualization and notification delivery. Furthermore, user evaluation involving 20 participants achieved an overall satisfaction score of 4.50 out of 5, indicating positive acceptance of the proposed system. These findings demonstrate that SITCARE provides an effective and practical IoT based solution for promoting ergonomic awareness and healthier workplace behavior among office workers.